ALGORITHM FOR THE EVALUATION OF CHILDREN WITH SUSPECTED URINARY TRACT ANOMALIES - Tanja Kersnik Levart; Robert Kordič (The Society for Children with Metabolic Disorders, 2023)
In the present review article "Algorithm for the evaluation of children with suspected urinary tract anomalies", an updated algorithm for evaluation of children in whom urinary tract anomalies are suspected is presented. The algorithm is based on the currently recommended classification of antenatal and postnatal urinary tract dilatation (UTD-A: antenatal urinary tract dilatation; UTD-P: postnatal urinary tract dilatation). The authors focus on the evaluation of children with UTD P, while guidelines for UTD A are presented in detail in the article "Prenatal diagnostics of congenital kidney and urinary tract anomalies". At the end of this article, the authors focus on indications and guidelines for children with urinary tract anomalies in whom urologic procedures are needed.